Interdependence of the manifestation of cognitive functions and sports success among young dancers - V. V. Myshko (H.S. Skovoroda Kharkiv National Pedagogical University, 2018)
Objective: To study the relationship between the level of cognitive abilities and the success of young dancers. Material: 24 sportsmen, who specialize in sports dances, aged 15-16, were examined. Cognitive abilities were studied by tests of perception, processing and decision-making on verbal stimuli - "establishing regularities" and non-verbal stimuli - "numerical comparison". Performance in sports dances was evaluated according to five international criteria. Statistical processing of mathematical data, pedagogical observations was used. Results: It is established that the success in sports dances is conditioned by the high level of manifestation of cognitive functions: attention, speed of visual perception, and increased level of operative and logical thinking in the processing of verbal information. High efficiency in the processing of stimuli in the verbal test of successful athletes, as compared to another group, indicates a high level of qualitative characteristics of mental functions of perception, processing of information and decision making. At the same time, the attention of successful athletes due to the speed of processing of information increases, which is reflected in lowering the level of efficiency and stability when performing the test for processing non-verbal information. Conclusions: The manifestation of success in sports dances is related to the level of development of cognitive functions: attention, verbal perception and operative and logical thinking. In the group of more successful athletes, the advantage of high-speed response characteristics in the cognitive test for non-verbal information was found. At the same time, in the group of athletes with reduced performance in sports dances, the qualitative characteristics of perception, analysis and decision making in the processing of non-verbal information are the best.